RECOMMENDATIONS OF THE EUROPEAN PHARMACOPOEIA «ADJUSTMENT OF CHROMATOGRAPHIC CONDITIONS» AND THEIR RESTRICTIONS FOR THE METHODS OF IMPURITIES DETERMINATION - N. A. Epshtein; V. L. Sevastianova; A. I. Koroleva (Разработка и регистрация лекарственных средств, 2019)
The recommendations of admissible corrections of the chromatographic conditions provided in chapter 2.2.46 of the European Pharmacopeia in the section "Adjustment of chromatographic conditions" are examined. Based on experience of the investigation of robustness of HPLC and UPLC methods and literary data, the article points out which of these recommendations are not suitable or have significant restrictions for the methods of impurities determination. An example that confirms some of the specified restrictions is given. For methods for determining impurities, it is recommended: to use admissible corrections of the chromatographic conditions from chapter 2.2.46 of the European Pharmacopeia, in section "Adjustment of chromatographic conditions" only in the absence of closely located or partially overlapping peaks of impurities not used for control of the resolution of chromatographic system on the chromatograms of the test solution of pharmaceutical substance / drug at the end of its shelf-life or on the chromatograms of the sample solutions after stress testing; an alternative condition is the absence of such peaks on the chromatograms of the solutions obtained under stress testing with the drug substance; to set admissible limits for the change (corrections) of the chromatographic conditions on the basis of the investigation of the robustness of the methods, and to include them, if necessary, in the methods.